2021
DOI: 10.1080/17425255.2021.1879049
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of predictors for β-lactam antibiotic exposure during empirical treatment in critically ill patients

Abstract: Introduction: : Emerging studies suggest that antibiotic pharmacokinetics (PK) are difficult to predict in critically ill patients. The high intra-and inter-patient PK variability makes it challenging to accurately predict the appropriate dosage required for a given patient. Identifying patients at risk could help clinicians to consider more individualized dosing regimens and perform therapeutic drug monitoring. We provide an overview of relevant predictors associated with target (non-)attainment of β-lactam a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Identifying patients at risk could help clinicians consider individualized dosing regimens and perform targeted use of TDM. 31 Relevant predictors related to target (non) achievement of beta-lactam antibiotics in critically ill patients have been well described, but their practical application has not yet been determined. Assessment tools (eg, MeroRisk Calculator 32 ) to identify patients at risk for target nonattainment could provide guidance and facilitate the implementation of beta-lactam TDM.…”
Section: Discussion Gap Analysis and Outlookmentioning
confidence: 99%
“…Identifying patients at risk could help clinicians consider individualized dosing regimens and perform targeted use of TDM. 31 Relevant predictors related to target (non) achievement of beta-lactam antibiotics in critically ill patients have been well described, but their practical application has not yet been determined. Assessment tools (eg, MeroRisk Calculator 32 ) to identify patients at risk for target nonattainment could provide guidance and facilitate the implementation of beta-lactam TDM.…”
Section: Discussion Gap Analysis and Outlookmentioning
confidence: 99%
“…It is well-known that the variability of PK of drugs in critically ill patients is very high [ 33 ], and clinical trials to estimate the PK parameters in this population must include a high number of patients; additionally, population models are recommended. In this regard, our study presents a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Currently, TDM of beta-lactams for efficacy in critically ill patients can be advised in individual cases with risk factors for target nonattainment. 67…”
Section: Antibioticsmentioning
confidence: 99%
“…3 In a recent review, male sex, younger age, and augmented clearance were shown to be significant predictors for target nonattainment of beta-lactams in critically ill patients. 67 Beta-lactams are time-dependent antibiotics and their PDT is commonly described as the percentage of a period in which free (f) concentrations exceed the MIC (% fT . MIC).…”
Section: Beta-lactamsmentioning
confidence: 99%